Existence and pattern of sleep-related breathing disorders in patients diagnosed with bronchial asthma - Saroj Kumari Meena; Rajnish Gupta; Manmohan Puri (Monaldi Archives for Chest Disease, 2024)
Asthma and obstructive sleep apnea (OSA) are commonly prevalent diseases, and both can co-exist to result in an alternate overlap syndrome, where a bidirectional relationship can adversely affect each other. This study aimed to determine the existence and pattern of sleep-related breathing disorders in subjects with bronchial asthma. It was prospectively conducted at the National Institute of Tuberculosis and Respiratory Diseases, New Delhi, in diagnosed cases of bronchial asthma. A subjective assessment of sleepiness was done using the Epworth sleepiness scale (ESS). All subjects underwent overnight polysomnography (PSG) in the Sleep Laboratory of the Institute. A total of 70 subjects were screened, and among them, finally, 30 were enrolled. The mean age of the subjects was 37.53±11.21 years, the mean body mass index (BMI) was 26.4±5.58 kg/m2, the mean ESS score was 3.1, and 80% of the subjects were male. After PSG, OSA (apnea hypopnea index >5/hour) was found in 63% (19/30) of the patients, of whom 43% had mild OSA, 10% had moderate OSA, and 10% had severe OSA. 10% (3/30) had nocturnal oxygen desaturation, while none had sleep hypoventilation. Patients with OSA compared to those without OSA had a higher BMI, more co-morbid allergic rhinitis, severe bronchial asthma, and a worse percentage of predicted forced expiratory volume in the first second. The study showed high detection rates of OSA in bronchial asthma patients. Hence, asthma patients should be evaluated for OSA.